Mathematics Critical Thinking Reviewed from Self-efficacy and Motivation of Learning in Arias Learning (Journal of Primary Education, 2019)
The ability to think critically and mathematically is the most important goal taught in mathematics learning. The purpose of this study was: analyzing the increase in critical thinking skills, describing the increase in critical thinking skills in terms of self-efficacy, and describing the increase in critical thinking skills in terms of learning motivation. The type of research was mixed methods research, with a sequential explanatory strategy. The sample of this research was the VII-A grade students of Public Junior High School 8 Cirebon City. Data collection was done by test, observation, and interview. Quantitative data were obtained from tests, and qualitative data were obtained from observations and interviews. Quantitative results are then triangulated with qualitative data. The results showed that there was an increase in critical thinking skill through the ARIAS model; students with high self-efficacy had high critical thinking skills; students with medium self-efficacy had medium or low critical thinking skills. Students with low self-efficacy had medium or low critical thinking skill; learning motivation has a strong relationship with critical thinking. Students with high learning motivation have high critical thinking skills. Students with medium learning motivation have medium critical thinking skills. Students with low learning motivation have low critical thinking skills.